The Effect of Service Quality on Fast Food Restaurant Customer Satisfaction: The Effect of Service Quality on Fast Food Restaurant Customer Satisfaction - Arinta Dea Puspita; M Jihadi (Universitas muhammadiyah malang, 2023)
This study aims to test the impact of service quality and customer satisfaction. This study uses a quantitative method using SPSS Application 26.0. The research population is all consumers at Prime Chicken of fast food restaurants. The sample was taken by 100 respondents and the data source used was the primary data obtained by disseminating the questionnaire. Methods of data analysis from research using correlation coefficient, determination coefficient and simple linear regression test. Based on the calculation of the correlation coefficient to find out how much the interpretation between service quality to customer satisfaction is obtained by 0.869 which shows that there is a positive and very strong relationship between service quality and customer satisfaction at Prime Chicken. From the calculation of the Determined Coefficient (KD) of 0.755 and from simple linear regression analysis can be found the relationship between service quality and customer satisfaction Y = a + bX = (5.179 + 0.879X)